INOVASI PEMBELAJARAN BAHASA ARAB MELALUI MEDIA VIDEO INTERAKTIF DI ERA DIGITAL - Nunik Zuhriyah; M. Zunaidul Muhaimin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The development of digital technology has brought significant changes to language learning methods, including Arabic. This study aims to analyze the use of interactive video media as an innovation in Arabic language learning in the digital age, as well as its impact on student motivation and learning outcomes. The study employs a qualitative approach using a case study method conducted at MA Al-Fatah Badas, with the subject being the 10th-grade class. Data was collected through observation, interview and documentation then analyzed descriptively. The results indicate that the use of interactive video enhances student engagement, facilitates understanding of the material, and fosters interest in learning Arabic. Interactive features such as quizzes, reflective questions, and learning path options provide a more participatory and personalized learning experience. Challenges identified include limited digital literacy among some teachers and insufficient technological facilities at the school. Thus, interactive videos can serve as an innovative solution to optimize Arabic language learning, particularly when supported by teacher training and adequate infrastructure.